Timing of hypoxia PET/CT imaging after 18F-fluoromisonidazole injection in non-small cell lung cancer patients - Bourigault, P; Skwarski, M; Macpherson, RE; Higgins, GS; McGowan, DR (Springer, 2022)
Positron emission tomography (PET)/computed tomography (CT) using the radiotracer 18F-Fluoromisonidazole (FMISO) has been widely employed to image tumour hypoxia and is of interest to help develop novel hypoxia modifiers and guide radiation treatment planning. Yet, the optimal post-injection (p.i.) timing of hypoxic imaging remains questionable. Therefore, we investigated the correlation between hypoxia-related quantitative values in FMISO-PET acquired at 2 and 4 h p.i. in patients with non-small cell lung cancer (NSCLC). Patients with resectable NSCLC participated in the ATOM clinical trial (NCT02628080) which investigated the hypoxia modifying effects of atovaquone. Two-hour and four-hour FMISO PET/CT images acquired at baseline and pre-surgery visits (n = 58) were compared. Cohort 1 (n = 14) received atovaquone treatment, while cohort 2 (n = 15) did not. Spearman’s rank correlation coefficients (ρ) assessed the relationship between hypoxia-related metrics, including standardised uptake value (SUV), tumour-to-blood ratio (TBR), and tumour hypoxic volume (HV) defined by voxels with TBR ≥ 1.4. As the primary imaging-related trial endpoint used to evaluate the action of atovaquone on tumour hypoxia in patients with NSCLC was change in tumour HV from baseline, this was also assessed in patients (n = 20) with sufficient baseline 2- and 4-h scan HV to reliably measure change (predefined as ≥ 1.5 mL). Tumours were divided into four subregions or distance categories: edge, outer, inner, and centre, using MATLAB. In tumours overall, strong correlation (P < 0.001) was observed for SUVmax ρ = 0.87, SUVmean ρ = 0.91, TBRmax ρ = 0.83 and TBRmean ρ = 0.81 between 2- and 4-h scans. Tumour HV was moderately correlated (P < 0.001) with ρ = 0.69 between 2- and 4-h scans. Yet, in tumour subregions, the correlation of HV decreased from the centre ρ = 0.71 to the edge ρ = 0.45 (P < 0.001). SUV, TBR, and HV values were consistently higher on 4-h scans than on 2-h scans, indicating better tracer-to-background contrast. For instance, for TBRmax, the mean, median, and interquartile range were 1.9, 1.7, and 1.6–2.0 2-h p.i., and 2.6, 2.4, and 2.0–3.0 4-h p.i., respectively. Our results support that FMISO-PET scans should be performed at 4 h p.i. to evaluate tumour hypoxia in NSCLC.